Developing Realistic Mathematics Education Material to Build Students Mathematical understanding Concepts Grade VII Junior High School on Linear Equation in Two Variables - Aris Budiyanto; Ismah Ismah (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
The student understanding about mathematical concept, especially on the topic of linear equation in two variables was importance. Aim of this study to develop mathematic material based on Realistic Mathematics Education to build students mathematical concept understanding. The material was developed upon 4-D model of Thiangrajan and was modified to be defined, designed, and developed. Therefore the realistic mathematic education instruction had good contribution on students thinking process. Population of this study are whole students grade VII junior high school of Bina Insan Mandiri and subject consist of ten students who were chose by purposive sampling based on evaluation test and students activity trough instructions. The developed material validated with descriptive analysis while quantitative data were calculated with score average. Based on experts the material was developed has been represented valid and effectiveness criteria based on students tested evaluation, and suitable to the instruction process.